Organocatalytic Asymmetric Synthesis of 2,3′-Connected Bis-Indolinones by Mannich Reactions of N-Acetylindolin-3-ones with Isatin N-Boc Ketimines - Gajulapalli, V. Pratap Reddy; Jafari, Ehsan; Kundu, Dipti S.; Mahajan, Suruchi; Peuronen, Anssi; Rissanen, Kari; Enders, Dieter (Synthesis, 2017)
A highly diastereo- and enantioselective Mannich reaction of N-acetylindolin-3-ones with isatin N-Boc ketimines to form 2,3′-connected bis-indolinones is developed employing a low loading of a readily available bifunctional thiourea catalyst. The asymmetric synthesis connects two indolinones via a vic-diamine unit and generates two neighboring stereocenters.
Keywords: asymmetric synthesis; indolinone; bifunctional thiourea; organocatalysis; Mannich reaction